(untitled) (Fiep Bulletin - online, 2014)
This article starts by commenting on the report presented by Pierre SEURIN during the opening of the World Congress of Physical Education, in Brussels, on July, 1st 1973, and follows on presenting the most important happenings and facts which contributed to the formation of today?s FIEP. The first of these facts was the foundation of the "Fédération Internationale de Gymnastique Educative" (F.I.G.E.) in 1923. After seven difficult years – due to some opposition to the Swedish conceptions of the entity and some problems regarding the authority to organize international contests –, FIGE changes its title to "Fédération Internationale de Gymnastique Ling" (F.I.G.L.). It was only in 1953, during the World Congress in Istanbul that the new title, “Fédération Internationale d?Éducation Physique”, F.I.E.P., was adopted.There is a thorough list of the most relevant events organized or sponsored by FIEP, as well as of those to which FIEP was engaged only as a participant. The author also registers the names of some of FIEP?s most brilliant minds and registers some of their major actions.